Analysis of Teacher Creativity in Learning English during the Covid-19 Pandemic at SMP Katolik Pelita Bangsa - Linerda Tulaktondok; Matius Tandi Kombong; Sushy Teko Patanduk (Universitas Cokroaminoto Palopo, 2022)
Education is an effort to educate the nation's life and also to improve the quality of human life through a learning process for students to understand, understand and be more critical in thinking, including learning English. For this reason, the role and position of the teacher is very strategic in national development, especially in the field education. During the Covid-19 pandemic, online learning demanded teacher creativity in designing and implementing education, which was needed so that online learning could run well. The purpose of this study is to find out how creative teachers are in learning English during the Covid-19 pandemic. Data were obtained from 2 English teachers at Pelita Bangsa Catholic Middle School. The instrument questions in the interview were prepared with reference to the 5 main topics of the creative teacher category according to Abedini & Broujeni (2016), namely lesson presentation, class management/management, assignments, teacher-student interaction, and teacher character. The creativity of teachers in learning English at SMP Katolik Pelita Bangsaduring the Covid-19 pandemic was carried out online, both non-interactive online and interactive online. During non-interactive learning through learning videos. The teacher makes learning videos according to the predetermined lesson plans and then uploads them on his YouTube channel. Presentation of learning material using videos made with their own creations which after being uploaded to YouTube then the video link is sent to students. The video already contains material explanations and examples as well as exercises and assignments that students must do. During non-interactive learning through Youtube, e-learning, and Google Classroom, then during interactive learning through Zoom meetings. Everything went well because it was supported by the character of the teacher who was disciplined, punctual, creative and always motivated his students.